Advancements in Forensic DNA Analysis and Its Role in Sustainable Justice Systems (Exoneration of Wrongfully Convicted Suspects as an Example) - نووری علی سلیم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This comprehensive study examines the critical role and effects of forensic DNA analysis in modern criminal justice systems, emphasizing its alignment with UN Sustainable Development Goal 16 (Peace, Justice, and Strong Institutions). Forensic DNA evidence plays a pivotal role in accurately identifying perpetrators, linking suspects to crime scenes, and exonerating innocent individuals wrongfully detained. By reducing wrongful convictions and resolving serious crimes such as theft, murder, and sexual assault more efficiently, forensic advancements strengthen the rule of law and improve institutional accountability. The study incorporates data-driven insights, international comparisons, and case studies—highlighting the importance of continued progress in forensic science. Special attention is given to ethical frameworks and policy recommendations guiding DNA practices within legal systems like that of the Kurdistan Region.